The zero-address form in the Japanese address system - Suyana, Yayan; Suhandano, Suhandano; Hariri, Tatang (Universitas Dian Nuswantoro, 2022)
In the Japanese language, there were various forms of address. For example, the use of the second pronoun; anata (you), kimi (you), self-name; Nakamura, Yamaguchi, kinship names; okaasan (mother), otousan (father), name of the profession; and sensei (teacher/doctor). In addition to the various address types, the zero forms of address were also known, namely the implicit use of address words. For example, address words in the form of zero were address (aisatsu); ohayou gozaimasu (good morning), irasshaimase (welcome), and sumimasen (sorry). The form of address adopted in this study was the zero-address form. This study would find the various forms and variations of zero-address. In addition, it also examined the functions and factors that influenced the use of zero-address by the sociolinguistic and pragmatics approach. This study found that there are four variations of the zero-address form, namely (1) the form of greeting; (2) the form of an exclamation or interjection; (3) the form of an interrogative sentence; and (4) the form of declarative sentences. There are two kinds of greeting, namely formal and informal. The function of the zero-address is to show respect, closeness, attract attention, and notification/statement. Factors that influence the use of zero greetings are social status, social distance, situation, and identity of the speaking actor.